Organophosphate poisoning at Chris Hani Baragwanath Academic Hospital 2012 - 2015 - Bruins, Joanne (My University, 2018)
Background Organophosphate poisoning causes significant morbidity and mortality globally. Patients with acute organophosphate poisoning are frequently admitted to the Chris Hani Baragwanath Academic Hospital (CHBAH), and yet, there is little literature assessing any of the aspects of these admissions. Objectives To determine the demographic profile, common clinical and biochemical findings, including the average pseudocholinesterase (PCHE)/red cell cholinesterase (RCC) levels, use of prognostic tools (APACHE II), management and outcome of adult patients admitted to the high care area (HCA) and intensive care unit (ICU) at CHBAH. Methods A retrospective data analysis of hospital records for 129 patients admitted to the HCA and ICU at CHBAH, for the period 2012 to 2015 was undertaken. The demographic profile (including the reason for ingestion), clinical and biochemical presentation of the patients was determined, and from their management notes, their requirement for ventilation, and duration thereof, the duration of ward stay and subsequent mortality rates were calculated. The use of a prognostic tool (APACHE II score) and the average enzyme inhibition levels demonstrated by the patients admitted to these units, was assessed. Results Of the 129 patients, the median age was 30 years with 68.2% being male patients. In keeping with the population served by CHBAH there was a predominance of African patients (99.2%). The most common clinical finding was pinpoint pupils (96.1%) followed by a Glasgow coma score <13 (85.3%), fasciculations (60.5%), diarrhoea (37.2%), and seizures (10.1%). The majority of the study population was admitted to the HCA (52.7%). The majority of the patients in both the ICU and HCA (99.2%) required ventilator support, with both the biochemical and arterial blood gas profile of the patients supporting this need. The mean duration of ward stay was 6.8 days for ICU (SD ±6.4) and 3.7 days for HCA (SD ±5.2). The overall mortality rate for both wards was 5.4%. Standard treatment was intravenous atropine, no oxime was administered. Both PCHE and RCC results reflected low levels of enzyme activity. The APACHE II score was underutilized and therefore we could not comment on its prognostic value in our setting. Conclusion: The findings of this study underscore the frequent use of organophosphate compounds as a means of deliberate self-harm in the Soweto area. This cohort constitutes the group of more severely affected patients, as almost all required ventilator support. The mortality rate is significant despite this being a treatable conditioned, and the impact on limited resources is great. Further studies in other institutions across the country, which include those patients who do not require ventilator support, is likely to highlight the magnitude of the consequences of organophosphate poisoning in our country, particularly with respect to causes of death in young people and the burden on healthcare resources.
A research report submitted to the University of the Witwatersrand, Johannesburg in fulfillment for the requirements of the degree of Master of Medicine, 2018
Keywords: Organophosphate Poisoning; Intensive Care Units